Organization of independent work in the training of future teachers of musical art: modern challenges and realities - Rastruba, Tetiana (Professional Art Education, 2023)
The purpose of the article is to determine the most effective model of building a systematic organization of independent work of future music teachers during their professional training. Methods and methodology . The research is based on the leading positions of scientists regarding the organization of independent work in the preparation of future teachers of musical art based on the principles of a comprehensive approach. The scientific novelty of the article lies in reflecting the concept of implementation and the main requirements for the implementation of independent work of students of art specialties in the process of their professional training. Recommendations are given on the use of the time budget for independent work by future music teachers; some aspects of digitalization of independent work are highlighted. Results . Updating attention to the main steps of organizing the independent work of future music teachers during their professional training. The principles of goal-setting, individualization, gradualism and systematicity, activity, control and feedback, use of modern technological means are highlighted as key in solving the issue of organizing students’ independent work. Its types, forms and methods are analyzed. Attention is drawn to the modern teacher’s understanding of his own role in the successful implementation of independent work by the student, as a consultant, facilitator , coach . The success factors of organizing independent work have been determined: self-motivation , time management, goal setting, constant practice and training, self-organization and support. An attempt was made to outline a modern model of organizing independent work for the effective implementation of the educational process in the preparation of future music teachers, which includes: design and planning, interactivity and the use of information and communication technologies, the formation of creative activity, independent research and collective participation.